Pengembangan E-Book Petunjuk Praktikum Literasi Lingkungan Berbasis Kearifan Lokal Kabupaten Malang - Diana Kusumaningrum; Yulia Eka Yanti (Peneliti.net, 2021)
Environmental literacy is one of the 21st century skills that are needed by students. However, this environmental literacy ability is still not empowered in schools, especially elementary schools in Malang Regency. In addition, Malang local wisdom is also starting to be abandoned. Therefore, a guide book is needed to empower and hone environmental literacy skills and preserve Malang local wisdom for elementary school students. This research is a research and development with Borg & Gall development model. The results of the study indicate that this e-book of environmental literacy practicum based on local wisdom is feasible to use.